Analisa Sarana Prasarana Bangunan: Studi Kasus Pasar Rakyat Krueng Geukueh, Aceh Utara - Husna, Asmaul; Fahrizal, Effan; Olivia, Sisca (Rifa'Institute, 2023)
The people's market which is the center of economic activity has the potential to drive the economy based on the people's economy, therefore it is necessary to make physical improvements to the people's market which was previously carried out a market analysis to maintain it. The government planned a market revitalization program, but many failed. Krueng Geukueh People's Market is one of the markets that has been built by the government but not according to existing standards. The purpose of this study was to determine the facilities and infrastructure 27 aspects of the criteria for SNI requirements for people's markets. The condition of this market infrastructure is not in accordance with the provisions of the people's market SNI, because some indicators of existing market facilities and infrastructure have not functioned as intended. This research uses a qualitative descriptive method. In collecting data used field observation, survey documentation. The results showed that the aspects of the people's market requirements studied were not effective for use by traders